Β-cell replacement sources for type 1 diabetes: a focus on pancreatic ductal cells. (August 2016) - Corritore, Elisa; Lee, Yong-Syu; Sokal, Etienne M.; Lysy, Philippe A.
Thorough research on the capacity of human islet transplantation to cure type 1 diabetes led to the achievement of 3- to 5-year-long insulin independence in nearly half of transplanted patients. Yet, translation of this technique to clinical routine is limited by organ shortage and the need for long-term immunosuppression, restricting its use to adults with unstable disease. The production of new bona fide β cells in vitro was thus investigated and finally achieved with human pluripotent stem cells (PSCs). Besides ethical concerns about the use of human embryos, studies are now evaluating the possibility of circumventing the spontaneous tumor formation associated with transplantation of PSCs. These issues fueled the search for cell candidates for β-cell engineering with safe profiles for clinical translation. In vivo studies revealed the regeneration capacity of the exocrine pancreas after injury that depends at least partially on facultative progenitors in the ductal compartment. These stimulated subpopulations of pancreatic ductal cells (PDCs) underwent β-cell transdifferentiation through reactivation of embryonic signaling pathways. In vitro models for expansion and differentiation of purified PDCs toward insulin-producing cells were described using cocktails of growth factors, extracellular-matrix proteins and transcription factor overexpression. In this review, we will describe the latest findings in pancreatic β-cell mass regeneration due to adult ductal progenitor cells. We will further describe recent advances in human PDC transdifferentiation to insulin-producing cells with potential for clinical translational studies.